Urus tadbir sebuah bandaraya Islam Malaysia: Kajian kes di Kota Bharu, Kelantan - Suhana Saad,; Marsitah Mohd Radzi, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
Governance in Malaysia is rather unique in that it is based on the socio-political system of the country and of the states within the country. It is thus within this praxis that the current Chief Minister of the opposition state of Kelantan forwarded a proposal of transforming the state’s city capital of Kota Bharu into an Islamic city with the slogan “developing with Islam”. The tagline, in a nutshell, means that Islamic values should define and shape the city way of life. This paper takes a closer look at the making of Kota Bharu into an Islamic city and assesses, in particular, its implications on the governance of the city by the Kota Bharu-Islamic City Council (MPKB-BRI). The MPKB-BRI governance philosophy has a fivefold principles, namely, knowledge, compliance, welfare, hygiene, and wellbeing. These should infuse the city’s development planning processes (development management, human development, economic development, and physical development) with desirable, relevant and applicable Islamic precepts. The city’s development plan is divided into two phases, the first (2006-2010) which emphasises on a public awareness raising programme about the Islamic city’s fivefold philosophy, and the second (2011-2015) which emphasises on the actual living up to the Islamic values the city embodies. The paper sums up that the greatest challenge in accomplishing the Islamic city mission of Kota Bharu is to ensure that the city’s populace properly understand the philosophy underlining an Islamic city which the MPKB-BRI is assigned to realise